Документальні матеріали щодо перебування на території України Владислава Міцкевича - Путова, Г.В. (Українська біографістика, 2010)
The publication contains a biography of Wladzislaw (Ladislas) Mickiewicz (1838–1926) — a prominent public and political fi gure, publisher, translator, and publicist, a son of the great Polish poet Adam Mickiewicz; it contais also a brief analysis of contents of documents, concerning the Mickiewicz family, which are kept in the collection of Central State Archives of Ukraine (Kiev); it represents the most outstanding documents, dedicated to sojourn of Wladzislaw Mickiewicz in the territory of Ukraine in 1861, as well.